Long-term prognosis of young breast cancer patients (≤40 years) who did not receive adjuvant systemic treatment: protocol for the PARADIGM initiative cohort study - Dackus, Gwen Mhe; Ter Hoeve, Natalie D; Opdam, Mark; Vreuls, Willem; Varga, Zsuzsanna; Koop, Esther; Willems, Stefan M; Van Deurzen, Carolien Hm; Groen, Emilie J; Cordoba, Alicia; Bart, Jos; Mooyaart, Antien L; et al. (BMJ open, 2017)
INTRODUCTION: Currently used tools for breast cancer prognostication and prediction may not adequately reflect a young patient's prognosis or likely treatment benefit because they were not adequately validated in young patients. Since breast cancers diagnosed at a young age are considered prognostically unfavourable, many treatment guidelines recommend adjuvant systemic treatment for all young patients. Patients cured by locoregional treatment alone are, therefore, overtreated. Lack of prognosticators for young breast cancer patients represents an unmet medical need and has led to the initiation of the PAtients with bReAst cancer DIaGnosed preMenopausally (PARADIGM) initiative. Our aim is to reduce overtreatment of women diagnosed with breast cancer aged ≤40 years. METHODS AND ANALYSIS: All young, adjuvant systemic treatment naive breast cancer patients, who had no prior malignancy and were diagnosed between 1989 and 2000, were identified using the population based Netherlands Cancer Registry (n=3525). Archival tumour tissues were retrieved through linkage with the Dutch nationwide pathology registry. Tissue slides will be digitalised and placed on an online image database platform for clinicopathological revision by an international team of breast pathologists. Immunohistochemical subtype will be assessed using tissue microarrays. Tumour RNA will be isolated and subjected to next-generation sequencing. Differences in gene expression found between patients with a favourable and those with a less favourable prognosis will be used to establish a prognostic classifier, using the triple negative patients as proof of principle. ETHICS AND DISSEMINATION: Observational data from the Netherlands Cancer Registry and left over archival patient material are used. Therefore, the Dutch law on Research Involving Human Subjects Act (WMO) is not applicable. The PARADIGM study received a 'non-WMO' declaration from the Medical Ethics Committee of the Netherlands Cancer Institute - Antoni van Leeuwenhoek hospital, waiving individual patient consent. All data and material used are stored in a coded way. Study results will be presented at international (breast cancer) conferences and published in peer-reviewed, open-access journals.
Keywords: Registries; receptory pro estrogeny; exprese genu; Humans; Gene Expression; registrace; kohortové studie; receptory progesteronu; dospělí; receptor erbB-2; lidé; časové faktory; Cohort Studies; Adult; breast tumours; Breast Neoplasms; Receptors, Estrogen; epidemiology; prognóza; výzkumný projekt; Receptors, Progesterone; Receptor, ErbB-2; nádory prsu; Research Design; histopathology; Time Factors; Prognosis